The Impact of COVID-19 Vaccination on the Social Participation of Immunocompromised Persons – Results of a Multicenter Observational Study - Heesen, Gloria; Schröder, Dominik; Müller, Frank; Hummers, Eva; Klawonn, Frank; Mikuteit, Marie; Niewolik, Jacqueline; Steffens, Sandra; Cossmann, Anne; Behrens, Georg; Dopfer-Jablonka, Alexandra; Heinemann, Stephanie (Frontiers in Public Health, 2022)
Immunocompromised persons are at an increased risk for a severe SARS-CoV-2 infection and their safety behaviors may influence their social participation. Vaccinated persons have a lower incidence of infection and severe disease when infected compared to non-vaccinated persons. Therefore, their behavior may change and their social participation may increase after a complete vaccination. The aim of this study was to explore social participation of immunocompromised persons before and after complete COVID-19 vaccination. Between March and September 2021, 274 immunocompromised participants were recruited. Survey data were collected at baseline and follow-up from 194 participants including the Index for the Assessment of Health Impairments [IMET], Patient Health Questionnaire-4 [PHQ-4], subjective health status and quality of life. At baseline, participants were not yet completely vaccinated. Complete vaccination was achieved prior to the follow-up questionnaire. IMET scores decreased significantly at follow-up, indicating a higher social participation after complete vaccination. PHQ-4, subjective health status and quality of life did not differ between baseline and follow-up. There were no significant differences across sociodemographic factors. Significant PHQ-4 differences were observed regarding the population size of the participants' home community. Social participation of immunocompromised persons in our study increased after COVID-19 vaccination. Therefore, social participation should be explored further, especially with regards to the impact of vaccination on groups with a high health risk.